The impact of visual search in Chinese children with developmental dyslexia on reading comprehension: the mediating role of word detection skill and reading fluency - Meng, Hu; Yao, Ru; Zhang, Pan; Wang, Jialei; Zhang, Yajing (Frontiers in Psychology, 2024)
Introduction Previous research has highlighted the influence of visual search (VS) on reading comprehension (RC); however, the underlying mechanisms of this effect remain poorly understood, particularly in children with reading disabilities. This study explores disparities in VS, word detection skills (WD), reading fluency (RF), and RC between Chinese children with developmental dyslexia (DD) and their typically developing peers across different age groups. Methods The sample comprised 191 students from grades 2, 4, and 6, including 92 children with dyslexia and 99 chronological age-matched controls. Variance analysis was used to examine differences in VS, WD, RF, and RC performance. Structural equation modeling (SEM) was employed to assess the relationships among these variables. Results Children with DD performed significantly worse than their typically developing peers on VS and RC tasks, with the most notable differences emerging in the middle and higher grades. Additionally, children with DD showed weaker WD skills and RF, with these disparities evident across all grade levels. SEM indicated that VS directly influences RC, with WD and RF serving as mediators in the relationship between VS and RC. Discussion These findings elucidate the complex interplay between visual processing and linguistic skills in reading development, particularly within the Chinese language context. The study underscores the importance of targeted interventions for children with dyslexia, emphasizing strategies that address the unique challenges these learners face in Chinese reading environments.